ANALISIS EFEKTIVITAS BIAYA (CEA) PENGOBATAN KOMBINASI DAN OAT PADA PASIEN TUBERKULOSIS PARU DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Sinaga, Alex; Berutu, Astini (Universitas Imelda Medan, 2022)
Tuberculosis (TB) is an infectious infectious disease caused by the bacterium Mycobacterium tuberculosis that can attack various organs, especially the lungs. Treatments that can be done in patients with pulmonary TB are treatments such as OAT (anti-tuberculosis drugs) which can be divided into single OAT and anti-tuberculosis drugs. combination drugs (drugs containing two or more active ingredients combined in one dosage form while maintaining the appropriate dose). This study aims to find out which treatment is more effective and cost-effective for pulmonary TB patients at Imelda Indonesian Workers Hospital in Medan. This research is a cohort study with snowball sampling technique. The conclusion of this study is that the ACER value of combination therapy is 75,490, and the ACER value of OAT is 92.130. The ICER value from the comparison of combination therapy and OAT was -5.762.